PERENNIALISME DALAM KEARIFAN LOKAL MASYARAKAT KOTESAN PRAMBANAN KLATEN - Kuswanjono, Arqom (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2010)
AbstractReligion is not sterile from the understanding and interpretation of adherents. Religion does not enter in the empty space of culture and the human mind. It will always dialogue and dialectics with the thoughts that had previously been filled with a variety of views derived from education, social relations, views of family, local culture and others. In such circumstances. when a religion is accepted by any person or group of people will come out with a variety of interpretations.This article is the result of research done in the village of Kotesan, Prambanan, Klaten. In establishing and maintaining an understanding of reality of religious diversity, there are threepillars that support this diversity, namely religion, culture and ideology. Religion is integral part of society that guide and direct human behavior. Culture is the expression of internalized values and norms of society. Pancasila is the view of life that provides awareness of its position as the nation of Indonesia. The three pillars are moving in synergy so that diversity is not a reason for dissension.Keywords: perennialism, local wisdom.